Research of thermal load in an energy efficient mechatronic truck transmission considering energy losses - Panasenkov Dmitry; Pankratov Fedor; Kartashov Aleksandr; Gazizullin Ruslan (E3S Web of Conferences)
The article examines the heating of a truck’s energy efficient mechatronic transmission during operation of an electric motor in maximum power mode. Particular attention is paid to the process of modeling conjugate heat transfer and its impact on the energy efficiency of mechatronic transmission. To solve this problem, computational fluid dynamics (CFD) methods are used, in particular the finite volume method (FVM), which allows for an accurate assessment of heat flows between different environments inside the transmission. Analysis of thermodynamic processes occurring in mechatronic transmission is of great importance for optimizing its operation and increasing reliability. The simulation results demonstrate the influence of various factors, such as driving speed, loads and temperature conditions, on the efficiency of heat exchange and, as a result, on the energy efficiency of the entire vehicle. These research contribute to the development of more efficient cooling systems and improved performance of trucks.